Hybrid transatrial stent insertion for left atrial decompression in hypoplastic left heart syndrome with intact atrial septum. Issue 1 (13th August 2015) - Hermuzi, Antony; McBrien, Angela; De Rita, Fabrizio; McCheyne, Alan; Griselli, Massimo; O'Sullivan, John J.; Hasan, Asif; Crossland, David S.
Abstract : Objectives: To describe a novel strategy for the management of infants with hypoplastic left heart syndrome (HLHS) and intact atrial septum. Antenatally diagnosed infants are delivered in cardiac theatre and immediate left atrial decompression (LAD) using hybrid transatrial stent insertion (HTSI) via sternotomy is carried out. Background: HLHS with intact atrial septum is a condition incompatible with life following placental separation. Despite a number of reported strategies the survival of these infants remains much worse than those born with an adequate atrial communication. Immediate postnatal LAD is mandatory to allow consideration of active treatment. Methods: Single institution retrospective review of intention to carry out HTSI for LAD in infants with an antenatal diagnosis of HLHS intact atrial septum. Results: Two patients were delivered by planned caesarean section and transferred immediately to the prepared team in the adjacent cardiothoracic theatre. Birth weights were 3.2 Kg and 2.96 Kg. Clinical condition was poor with mean arterial PaO2 2.8kPa intubated with 100% inspired oxygen. HTSI was performed using premounted 7 × 17 mm stents (Visi‐Pro™, eV3 Endovascular, Plymouth, MN). Mean arterial PaO2 improved to 6.2 kPa. Mean time from surgical incision to LAD was 26 min. Bilateral pulmonary artery bands (BPAB) were then placed. No procedural complications occurred and both patients underwent subsequent surgical stage 1 Norwood at 6 and 10 days. Conclusions: In this high‐risk anatomical substrate, careful planning from accurate fetal diagnosis underpins the success of initial management. This early experience suggests that HTSI offers rapid and successful postnatal LAD with no procedural morbidity facilitating successful subsequent palliation. © 2015 Wiley Periodicals, Inc.